2010
DOI: 10.1242/jeb.048439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different glycaemic conditions on gene expression of neuropeptides involved in control of food intake in rainbow trout; interaction with stress

Abstract: ). Hyperglycaemic NSD conditions resulted in decreased mRNA levels of NPY and increased levels of CART and POMC in the hypothalamus as well as increased mRNA levels of CART and CRF in the hindbrain compared with hypo-and normoglycaemic conditions. HSD conditions in normoglycaemic fish induced marked changes in the expression of all peptides assessed: mRNA levels of NPY and CRF increased and mRNA levels of POMC and CART decreased in the hypothalamus, whereas the expression of all four peptides (NPY, POMC, CART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 34 publications
9
64
0
1
Order By: Relevance
“…However, we measured changes in the abundance of mRNA for different neuropeptides, such as NPY, POMC and CART, that are involved in the regulation of food intake (Volkoff et al, 2009) and for which we have demonstrated that their mRNA abundance was dependent on the glucose concentration in the medium (Conde-Sieira et al, 2010b), allowing us to suggest their relationship with central glucosensing mechanisms in rainbow trout. The increased glucose concentration in the medium elicited in controls decreased the mRNA abundance of NPY in hypothalamus and hindbrain and increased CART mRNA abundance in hypothalamus, in agreement with our previous in vivo ( Conde-Sieira et al, 2010b) and in vitro results (Aguilar et al, 2011) in the same species, thus reinforcing the validity of our experimental design. In the present study, we found that, in a way similar to that observed for glucosensing factors, CRF treatment induced a change in the response of mRNA abundance to changes in glucose concentration in the medium.…”
Section: Discussion the Effects Of Crf On Glucosensing-related Paramesupporting
confidence: 90%
See 1 more Smart Citation
“…However, we measured changes in the abundance of mRNA for different neuropeptides, such as NPY, POMC and CART, that are involved in the regulation of food intake (Volkoff et al, 2009) and for which we have demonstrated that their mRNA abundance was dependent on the glucose concentration in the medium (Conde-Sieira et al, 2010b), allowing us to suggest their relationship with central glucosensing mechanisms in rainbow trout. The increased glucose concentration in the medium elicited in controls decreased the mRNA abundance of NPY in hypothalamus and hindbrain and increased CART mRNA abundance in hypothalamus, in agreement with our previous in vivo ( Conde-Sieira et al, 2010b) and in vitro results (Aguilar et al, 2011) in the same species, thus reinforcing the validity of our experimental design. In the present study, we found that, in a way similar to that observed for glucosensing factors, CRF treatment induced a change in the response of mRNA abundance to changes in glucose concentration in the medium.…”
Section: Discussion the Effects Of Crf On Glucosensing-related Paramesupporting
confidence: 90%
“…The abundance of mRNAs for factors related to glucosensing capacity (GK, Glut2, Kir.6-like and SUR-like) and for peptides related to the control of food intake (NPY, POMC and CART) was assessed by qPCR as described previously for rainbow trout (Polakof et al, 2008a;Polakof et al, 2008b;Polakof et al, 2008c;Conde-Sieira et al, 2010b). Relative quantification of the target gene transcripts was performed using -actin gene expression as a reference, which was stably expressed in this experiment.…”
Section: Gene Expression Analysis By Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…We also demonstrated that these glucosensing systems are deregulated under stress conditions, like those associated with high stocking density (HSD), resulting in their inability to respond to changes in circulating glucose levels (Conde-Sieira et al, 2010a). Furthermore, the same stress conditions elicit reduced food intake and changes in the mRNA abundance of several peptides related to the control of food intake, including corticotropin-releasing factor (CRF) (Conde-Sieira et al, 2010b), that could be related to the well-known anorectic effect of stress in fish (Wendelaar Bonga, 1997;Bernier, 2006). Accordingly, we have recently demonstrated that the responses to changes in glucose levels of parameters related to glucosensing in the hypothalamus and hindbrain of rainbow trout are modified in the presence of CRF (Conde-Sieira et al, 2011), in a way comparable to that observed under stress conditions (Conde-Sieira et al, 2010a).…”
Section: Introductionmentioning
confidence: 95%
“…The analyses were carried out with 1 µl cDNA using the MAXIMA SYBR Green qPCR Mastermix (Thermo Scientific, Waltham, MA, USA), in 15 µl of PCR reaction containing 50-500 nmol l −1 of each primer. The mRNA abundance of transcripts of interest (COX4, CPT1c, CPT1d, FBPase, GLUT2, GK, Gnat3, HOAD, Kir6.x-like, LXRα, PK, PPARγ, SGLT-1, SREBP1c, SUR-like, T1R2, T1R3 and UCP2a) was assessed as described in the same species (Panserat et al, 2000(Panserat et al, , 2001Polakof et al, 2008cPolakof et al, , 2011bKolditz et al, 2008;Lansard et al, 2009;Cruz-Garcia et al, 2009;Conde-Sieira et al, 2010;Sánchez-Gurmaches et al, 2012;Polakof and Soengas, 2013;Librán-Pérez et al, 2013). The sequences and accession numbers of the primers used for each transcript are shown in Table 1.…”
Section: Mrna Abundance Analysis By Real-time Quantitative Rt-pcrmentioning
confidence: 99%